TINJAUAN HUKUM SANKSI PIDANA PADA PELAKU PENYEBARAN KONTEN PORNOGRAFI DI INTERNET - Rengga Fatma Jaya; Noenik Soekorini; Sri Astutik; Vieta Imelda Cornelis (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Abstrak. The development of the times is so rapid, the mode of spreading pornographic content has also spread through the internet. The formulation of the crime of pornography is also regulated in article 27 paragraph (1) of Law Number 11 of 2008 concerning Electronic Information and Transactions, which reads: "Every person intentionally and without right distributes and/or transmits and/or makes electronic information accessible and/or Electronic Documents that contain content that violates decency.”the formulation of the problem that will be raised in this thesis is: How is the law enforced for perpetrators of spreading pornographic content on the internet? What are the criminal sanctions for those who spread pornographic content on the internet? This type of research is normative legal research. Normative legal research is solving legal problems normatively which basically relies on a critical and in-depth study of library materials and legal documents that are relevant to the legal problems being studied. Conclusion: Legal review of the distribution of pornographic content on the internet according to Law number 1 of 2024 concerning the second amendment to Law number 11 of 2008 concerning electronic information and transactions, that content within the scope of information and electronic transactions which is included in the category of decency is several types of content pornography, namely in the form of writing, images or videos. Meanwhile, Legal sanctions for the purpose of distributing pornographic content on the internet according to Law Number 44 of 2008 concerning Pornography must meet the criminal elements for uploading decency content on social media according to Law Number 1 of 2024 concerning the second amendment to Law Number 11 of 2008 Regarding electronic information and transactions, content or sentences uploaded to social media services that contain elements of decency are distributed without any rights and become public consumption for users. other social media services. The legal consequences arising from the use of content containing decency on social media based on the criminal law in force in Indonesia are that you will be punished with imprisonment for a maximum of 6 (six) years and/or a fine of a maximum of IDR. 1,000,000,000.00 (one billion rupiah) in accordance with Article 45 of Law Number 1 of 2024. Second amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. Keywords: Criminal Sanctions, Distribution, Pornographic Content, Internet Abstrak. Perkembangan zaman yang begitu pesat, modus penyebaran konten pornografi pun juga merambah melalui internet. Rumusan tindak pidana pornografi juga diatur pada pasal 27 ayat (1) Undang-Undang Nomor 11 Tahun 2008 mengenai Informasi dan Transaksi Elektronik, yaitu berbunyi: “Setiap orang dengan sengaja dan tanpa hak mendistribusikan dan/atau mentransmisikan dan/atau membuat dapat diaksesnya Informasi Elektronik dan/atau Dokumen Elektronik yang memiliki muatan yang melanggar kesusilaan.”Penelitian ini menjelaskan penegakan hukum pelaku penyebaran konten pornografi di internet? Bagaimana sanksi pidana pelaku penyebaran konten pornografi di internet ? Penelitian hukum normatif adalah memecahkan masalah hukum secara normatif yang pada dasarnya bertumpu pada penelaahan kritis dan mendalam terhadap bahan- bahan pustaka dan dokumen- dokumen hukum yang relevan dengan permasalahan hukum yang dikaji. Kesimpulan penyebaran konten pornografi di internet menurut Undang-undang nomor 1 Tahun 2024 tentang perubahan kedua atas Undang-undang nomor 11 tahun 2008 tentang informasi dan transaksi Elektronik, Bahwa konten dalam lingkupan informasi dan transaksi elektronik yang termasuk dalam kategori kesusilaan adalah beberapa jenis konten pornografi yaitu dalam bentuk tulisan, gambar atau video. Sedangkan Sanksi hukum penyebaran konten pornografi di internet menurut Undang-undang Nomor 44 tahun 2008 tentang Pornografi harus memenuhi unsur pidana atas unggahan konten konten berbentuk kesusilaan pada media sosial menurut Undang-undang nomor 1 Tahun 2024 tentang perubahan kedua atas Undang-undang nomor 11 tahun 2008 tentang informasi dan transaksi Elektronik adalah konten-konten atau kalimat-kalimat yang diunggah kedalam layanan media sosial yang mengandung unsur kesusilaan disebar luaskan secara tanpa memiliki hak dan menjadi konsumsi publik bagi pengguna layanan media sosial lainnya. Akibat hukum yang timbul terhadap penggunaan konten yang mengandung kesusilaan pada media sosial berdasarkan hukum pidana yang berlaku di Indonesia adalah akan dipidana dengan pidana penjara paling lama 6 (enam) tahun dan/atau denda paling banyak Rp. 1.000.000.000,00 ( satu miliar rupiah) sesuai dengan Pasal 45 Undang-Undang Nomor 1 Tahun 2024 Perubahan kedua atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik. Kata Kunci: Sanksi Pidana, Penyebaran, Konten Pornografi, Internet